PREGNANCY AND CHILDBIRTH IN A YOUNG WOMAN WITH CONCOMITANT MUTATION IN LEIDEN AND PROTHROMBIN GENE G20210A - D. L. Kapanadze (IRBIS LLC, 2016)
Pregnancy and childbirth in women with genetic or acquired thrombophilia is usually associated with a high risk to both thrombotic and obstetric complications and fruit. Unambiguous answer to the question of routine screening for thrombophilia in women with a history of obstetric history does not exist until now. It should be noted that the physiological hypercoagulable inherent pregnant, often for the first time reveals the background congenital and / or acquired disorders of hemostasis, which previously could be asymptomatic. A history of fetal loss syndrome, severe obstetric complications (severe preeclampsia, severe  twin-platsentranoy failure, fetal death, premature detachment of the placenta), thromboembolism is an indication for the study of genetic thrombophilia and antiphospholipid syndrome.